Pengaruh Self Efficacy, Tolerance Risk, dan Emotional Intelligence Terhadap Entrepreneurship Intention - Nuri Annisa Fitri; Hisbullah Basri; Ima Andriyani (UNIVED Press, 2023)
This study aims to determine the effect of Self Efficacy, Tolerance Risk, and Emotional Intelligence on Entrepreneurship Intention. Respondents in this study were students of Tridinanti University Palembang at the Faculty of Economics. There are two methods used in this study, namely simple regression analysis and multiple regression. The first hypothesis, the linearity criteria are met and the calculated F value is 70,428 with a Sig value. = 0.000 < 0.05. There is a positive and significant effect of Self Efficacy on Entrepreneurship Intention. The second hypothesis, the linearity criteria are met, and the calculated F value is 67,192 with a Sig value. = 0.000 < 0.05. There is a positive and significant effect of Tolerance Risk on Entrepreneurship Intention. The third hypothesis, the linearity criteria are met, and the calculated F value is 149,578 with a Sig value. = 0.000 < 0.05. There is a positive and significant influence of Emotional Intelligence on Entrepreneurship Intention. The fourth hypothesis, the linearity criteria are met, and the calculated F value is 52,374 with a Sig value. = 0.000 < 0.05. There is a positive and significant influence of Self Efficacy, Tolerance Risk, and Emotional Intelligence on Entrepreneurship Intention.